Soft magnetic alloy and magnetic component
The development of a soft magnetic alloy with specific Cu cluster characteristics addresses the challenge of minimizing core loss in magnetic components, resulting in improved efficiency and performance.
Patent Information
- Application Number
- JP2023168543
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Existing soft magnetic alloys struggle to minimize core loss in magnetic components, which is a critical issue for efficient energy transfer and storage.
A soft magnetic alloy containing at least Fe and Cu, with specific Cu cluster characteristics, including a defined concentration distribution and aspect ratio, is developed. This alloy is optimized to have an average A/B ratio between 0.40 and 0.70, and a dispersion of A/B less than 0.13, which enhances the uniformity of Cu clusters and reduces core loss.
The optimized soft magnetic alloy achieves lower core loss in magnetic components, improving their efficiency and performance by ensuring uniform Cu cluster distribution and size uniformity of Fe-containing nanocrystals.
Smart Images

Figure 2025058548000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to soft magnetic alloys and magnetic components. [Background technology]
[0002] Patent Document 1 describes an alloy that, by setting the composition within a specific range, can obtain a core with reduced core loss.
[0003] Patent Document 2 describes a nanocrystalline soft magnetic alloy that contains Fe, B, P, and Cu and has improved soft magnetic properties by controlling various parameters that can be measured by a three-dimensional atom probe, such as the density of Cu clusters, within a specific range. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 3287481 [Patent Document 2] International Publication No. 2021 / 132254 Summary of the Invention [Problem to be solved by the invention]
[0005] It is an object of the present invention to provide a soft magnetic alloy that allows the production of magnetic components with reduced core loss. [Means for solving the problem]
[0006] In order to achieve the above object, the soft magnetic alloy according to the present invention comprises: A soft magnetic alloy containing at least Fe and Cu, The soft magnetic alloy includes at least one Cu cluster; In any cross section, the point with the highest Cu concentration in the Cu cluster is called point C, the longest diameter of the Cu cluster that passes through point C is called the Cu major axis, and the Cu concentration at point C is called C. max year, The Cu concentration of the soft magnetic alloy is C ave year, The Cu concentration is continuously (0.5×C max ) is the length of the part that is equal to or greater than A, The Cu concentration is continuously (2×C ave ) is the length of the part that is equal to or greater than B, The average A / B in the soft magnetic alloy is 0.40 or more and 0.70 or less.
[0007] The dispersion of A / B in the soft magnetic alloy (σ 2 ) may be less than 0.13.
[0008] C in the soft magnetic alloy max The average may be 9.9 at % or more and 52.1 at % or less.
[0009] The soft magnetic alloy may have a crystalline phase and an amorphous phase.
[0010] The soft magnetic alloy may be in the form of a thin ribbon.
[0011] The soft magnetic alloy may be in powder form.
[0012] The magnetic component according to the present invention includes the above-mentioned soft magnetic alloy. [Brief description of the drawings]
[0013] [Figure 1] 1 is an image showing the position of the Cu long axis in a Cu cluster. [Diagram 2] This is a graph in which the horizontal axis represents a line segment including the Cu major axis, and the vertical axis represents the Cu concentration. [Diagram 3] FIG. 1 is a schematic diagram of a single roll process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described.
[0015] The soft magnetic alloy according to this embodiment contains at least Fe and Cu.
[0016] The soft magnetic alloy may contain a crystalline phase and an amorphous phase. There is no particular limit to the content of the crystalline phase and the content of the amorphous phase in the soft magnetic alloy.
[0017] The soft magnetic alloy includes at least one Cu cluster 11 .
[0018] In this embodiment, the Cu cluster 11 is a cluster having a Cu concentration of the soft magnetic alloy of C ave Then, the concentration of Cu is (2 × C ave ) or more.
[0019] A Cu mapping image can be obtained by observing soft magnetic alloys using a three-dimensional atom probe (3DAP). Figure 1 shows an enlarged view of a Cu cluster, which will be described later. The brighter the area, the higher the Cu concentration. In particular, the Cu concentration is (2×C ave ) or higher appears brighter.
[0020] There is no particular limit to the observation range of 3DAP, but it should be at least 64,000 nm 3 More than 320,000 nm, preferably 320,000 nm 3 The shape of the observation area is not particularly limited. For example, it may be a rectangular parallelepiped of 40 nm x 40 nm x 200 nm.
[0021] The set observation range is divided into a cubic grid of 1 nm x 1 nm x 1 nm. The number of grids must be at least 64,000. For example, if the shape of the observation range is a rectangular parallelepiped of 40 nm x 40 nm x 200 nm, the set observation range is divided into 320,000 grids.
[0022] The number of Cu clusters used in the analysis is at least 100. If sufficient Cu clusters are not observed in the above analysis range, multiple observation ranges may be set for the same soft magnetic alloy, and each observation range may be observed, and the observation results may be added together.
[0023] Note that Cu clusters that are divided by the boundaries of the observation range are not taken into account. In other words, Cu clusters that are not entirely contained within the observation range are not taken into account. The same applies to the following descriptions (e.g., calculation of A / B).
[0024] In the soft magnetic alloy, granular Cu clusters 11 shown in FIG. 1 may be dispersed within the soft magnetic alloy.
[0025] For example, in the soft magnetic alloy, the average equivalent sphere diameter of the Cu clusters 11 may be 3.0 nm or more and 30 nm or less.
[0026] For example, in the soft magnetic alloy, the aspect ratio of the Cu clusters 11 may be 0.50 or more.
[0027] A / B is set as an index representing the uniformity of the concentration distribution in each Cu cluster 11. A method for setting A / B will be described below.
[0028] First, the point where the Cu concentration is highest in each Cu cluster 11 is identified, and this point is designated as point C. POINT C shown in FIG. 1 is the point where the Cu concentration is highest in the Cu cluster 11 shown in FIG.
[0029] Next, the longest diameter of the diameters of the Cu cluster 11 that pass through point C is defined as the Cu major diameter. A line segment 21 including the Cu major diameter is illustrated in FIG.
[0030] Next, the line profile of the Cu concentration is measured for the line segment 21 including the Cu major axis. Then, the line segment 21 including the Cu major axis is plotted on the horizontal axis, and the Cu concentration is plotted on the vertical axis. The results are shown in FIG.
[0031] The concentration of Cu at point C is C max Then, the point C is included on the major axis of Cu, and the concentration of Cu is continuously (0.5 × C max The length of the part where the Cu concentration is equal to or greater than (2 × C ave ) is the length of the part that is equal to or greater than B. The length of B is equal to the length of the major axis of Cu.
[0032] It can be interpreted that the smaller the A / B, the sharper the distribution of the Cu concentration, and the larger the A / B, the broader the distribution of the Cu concentration.
[0033] The average of A / B in the soft magnetic alloy is 0.40 or more and 0.70 or less. The average of A / B is obtained by calculating A / B for all Cu clusters 11 included in the observation range of the 3DAP and averaging them. Since the observation range is sufficiently large, the result of measuring all Cu clusters 11 included in the observation range may be the result of measuring all Cu clusters 11 in the soft magnetic alloy.
[0034] A magnetic core having a soft magnetic alloy in which the average A / B is 0.40 or more and 0.70 or less has lower core loss than a magnetic core having a soft magnetic alloy of the same composition except that the average A / B is less than 0.40 or exceeds 0.70.
[0035] A soft magnetic alloy with an average A / B of less than 0.40 or more than 0.70 can be interpreted as having many Cu clusters 11 in which the Cu concentration distribution from point C to the surface is too sharp or too broad, compared to a soft magnetic alloy with an average A / B of 0.40 or more and 0.70 or less. In a soft magnetic alloy with many such Cu clusters 11, the size and arrangement of nanocrystals containing Fe tend to be nonuniform. Therefore, it is considered that a magnetic core having a soft magnetic alloy with an average A / B of less than 0.40 or more than 0.70 tends to have high core loss.
[0036] Dispersion of A / B in soft magnetic alloys (σ 2) may be less than 0.13. When the variance of A / B is less than 0.13, the formation of Fe crystals becomes more uniform, and the core loss of the magnetic core having the soft magnetic alloy becomes lower. The variance of A / B is more preferably less than 0.10.
[0037] C in soft magnetic alloys max The average of may be 9.9 at% or more and 52.1 at% or less. max The average of C for all Cu clusters 11 included in the 3DAP observation range above is max The C in soft magnetic alloys is calculated and averaged. max By setting the average of 9.9 at % or more and 52.1 at % or less, the size and arrangement of the nanocrystals containing Fe can be made more uniform, and the core loss of the magnetic core having the soft magnetic alloy can be reduced. max The average of is more preferably 10.0 at % or more and 50.0 at % or less, even more preferably 15.0 at % or more and 40.0 at % or less, and even more preferably 23.1 at % or more and 40.0 at % or less.
[0038] The composition of the soft magnetic alloy according to this embodiment is not particularly limited except that it contains at least Fe and Cu, and is preferably within the range of composition (1) below.
[0039] Composition (1) has the following composition: The atomic ratio is expressed as the composition formula (Fe 1-( α + β ) CoαNiβ) 1-(a+b+c+d) M a Cu b X1 c X2 d and M is one or more selected from Nb, Hf, Zr, Ta, Mo, V, Ti, W and Cr; X1 is one or more selected from B, P, Si and C; X2 is one or more selected from Al, Mn, Ag, Zn, Sn, As, Sb, Ga, Bi, S, N, O, Ca, Mg, Au, rare earth elements, and platinum group elements; 0≦a≦0.150 0 <b≦0.050 0≦c≦0.300 0≦d≦0.050 α ≧ 0 β ≧ 0 0≦α+β≦0.500.
[0040] There is no particular limitation on the method for identifying the composition of the soft magnetic alloy, i.e., the types of M, X1, and X2 and the values of α, β, a, b, c, and d. For example, the composition of the soft magnetic alloy can be identified by a scanning transmission electron microscope (STEM), a transmission electron microscope (TEM), an energy dispersive X-ray spectroscopy (EDS), an electron energy loss spectroscopy (EELS), a fast Fourier transform (FFT) analysis of a TEM image, a powder X-ray diffraction (XRD) method, an X-ray fluorescence spectroscopy (XRF), an inductively coupled plasma atomic emission spectroscopy (ICP-AES), or the like.
[0041] The content of elements other than the above, that is, elements other than Fe, Co, Ni, M, Cu, X1 and X2, may be 0.1 mass % or less.
[0042] The content (a) of M may be 0≦a≦0.150, or 0≦a≦0.100.
[0043] Cu content (b) is 0 <b≦0.050であってもよく、0.001≦b≦0.050であってもよく、0.003≦b≦0.012であってもよい。
[0044] The content (c) of X1 may be 0≦c≦0.300, or 0.050≦c≦0.235.
[0045] The content (d) of X2 may be 0≦d≦0.050, or 0≦d≦0.015.
[0046] The Co content (α) relative to the total content of Fe, Co and Ni is not particularly limited and may be 0≦α≦0.500.
[0047] The Ni content (β) relative to the total content of Fe, Co and Ni is not particularly limited, and may be 0≦β≦0.500.
[0048] The Fe content relative to the total content of Fe, Co and Ni (1-(α+β)) is not particularly limited, and may be (1-(α+β))≧0.500.
[0049] The Fe content ((1-(α+β))×(1-(a+b+c+d))) in the soft magnetic alloy is not particularly limited, but may be 0.4125 or more and 0.885 or less. That is, it may be 41.25 at% or more and 88.5 at% or less. The lower limit of the Fe content is preferably 77.0 at% or more, and more preferably 79.8 at% or more.
[0050] The method for producing the soft magnetic alloy according to this embodiment will be described below.
[0051] Any method can be used for producing the soft magnetic alloy according to this embodiment, but an example of such a method is to produce a ribbon of the soft magnetic alloy by a single roll method.
[0052] In the single roll method, first, various raw materials such as pure metals of each metal element contained in the final soft magnetic alloy are prepared and weighed so as to have the same composition as the final soft magnetic alloy. Then, the pure metals of each metal element are melted and mixed to prepare a master alloy. The pure metals can be melted by any method, for example, by drawing a vacuum in a chamber and then melting by high-frequency heating. The master alloy and the final soft magnetic alloy usually have the same composition.
[0053] Next, the produced master alloy is heated and melted to obtain a molten metal (molten metal). There is no particular limitation on the temperature of the molten metal, but it can be set to 1000 to 1500°C, for example.
[0054] A schematic diagram of an apparatus used in the single roll method is shown in Fig. 3. In the single roll method according to this embodiment, molten metal 32 is sprayed from a nozzle 31 onto a roll 33 rotating in the direction of the arrow inside a chamber 35, thereby producing a ribbon 34 in the rotation direction of the roll 33. Note that in this embodiment, there is no particular limitation on the material of the roll 33. For example, a roll made of Cu is used.
[0055] In the single roll method, the thickness of the resulting ribbon can be adjusted mainly by adjusting the rotation speed of the roll 33, but the thickness of the resulting ribbon 34 can also be adjusted by adjusting, for example, the distance between the nozzle 31 and the roll 33, the temperature of the molten metal, etc. The thickness of the ribbon 34 is not particularly limited, but can be, for example, 10 to 50 μm.
[0056] The temperature of the roll 33 is arbitrary. It may be 30 to 70°C.
[0057] The atmosphere inside the chamber 35 is arbitrary. For example, it may be a vacuum or the air. It may also be an inert gas atmosphere.
[0058] By heat treating the obtained ribbon 34, Cu clusters can be generated in the soft magnetic alloy. Furthermore, nano-crystallization of Fe contained in the soft magnetic alloy can be appropriately promoted, so that the soft magnetic alloy has a crystalline phase and an amorphous phase.
[0059] The following describes the heat treatment conditions for making the A / B ratio in the soft magnetic alloy obtained after the heat treatment described below be 0.40 or more and 0.70 or less.
[0060] In order to set the A / B ratio in the soft magnetic alloy to 0.40 or more and 0.70 or less, it is important to carry out the first to third stages, which will be described later, in succession.
[0061] In the first stage, a gradual oxidation treatment is performed in an oxidizing atmosphere, which can promote the formation of Cu clusters in the soft magnetic alloy.
[0062] Specifically, first, the atmosphere in the chamber where the heat treatment is performed is set to an oxidizing atmosphere containing oxygen. The oxygen concentration may be 100 ppm or more and 100,000 ppm or less. It is preferable that the oxygen concentration is 500 ppm or more and 10,000 ppm or less. There is no particular limit to the gas contained in the atmosphere other than oxygen. For example, argon gas or nitrogen gas may be used. However, the hydrogen concentration is less than 50 ppm. Then, after the atmosphere is adjusted to an oxidizing atmosphere, the heat treatment is performed. First, the temperature in the chamber is heated to a temperature at which the gradual oxidation treatment is performed. There is no particular limit to the temperature at which the gradual oxidation treatment is performed. It may be 350°C or more and 430°C or less. There is no particular limit to the heating rate. For example, it may be 1°C / min or more and 100°C / min or less. Then, the temperature at which the gradual oxidation treatment is performed is maintained for a predetermined time. There is no particular limit to the predetermined time. For example, it may be 0.5 hours or more and 3.0 hours or less.
[0063] In the second stage, heat treatment is performed in an inert atmosphere, which allows the nanocrystallization of the Fe contained in the soft magnetic alloy to proceed appropriately and produces nanocrystals containing Fe.
[0064] Specifically, first, the atmosphere in the chamber is made into an inert atmosphere while maintaining the temperature for the first stage gradual oxidation treatment. Specifically, the oxygen concentration is made less than 50 ppm. The hydrogen concentration is still made less than 50 ppm. After that, the temperature in the chamber is heated to the temperature for the second stage heat treatment. There is no particular limit to the temperature for the second stage heat treatment. Although it varies depending on the composition of the soft magnetic alloy, it is made higher than the temperature for the gradual oxidation treatment. Specifically, the temperature for the second stage heat treatment is made higher than the temperature for the gradual oxidation treatment by 5°C or more. The temperature for the second stage heat treatment may be, for example, 410°C or more and 625°C or less. There is no particular limit to the heating rate. For example, it may be 1°C / min or more and 100°C / min or less. And there is no particular limit to the time for maintaining the temperature for the heat treatment. For example, it may be 0.5 hours or more and 3.0 hours or less.
[0065] In the third stage, a reduction treatment is performed in a reducing atmosphere. This removes the oxide layer formed on the surface of the soft magnetic alloy. Furthermore, the Cu concentration distribution in the Cu cluster is changed to make the Cu concentration distribution from point C of the Cu cluster to the surface uniform, and the dispersion of A / B (σ 2 ) can be reduced. This promotes structural relaxation of the Fe-containing nanocrystals generated in the second stage, making it easier for the size and arrangement of the Fe-containing nanocrystals to become more uniform.
[0066] Specifically, first, the inside of the chamber is cooled to a temperature at which the reduction treatment is performed while maintaining the inert atmosphere in the second stage. There is no particular limit to the cooling rate. For example, it may be 1°C / min or more and 100°C / min or less. There is no particular limit to the temperature at which the reduction treatment is performed. Although it varies depending on the composition of the soft magnetic alloy, it is lower than the temperature at which the heat treatment in the second stage is performed. Specifically, the temperature at which the reduction treatment is performed is lower than the temperature at which the heat treatment in the second stage is performed by 5°C or more. The temperature at which the reduction treatment is performed is, for example, 350°C or more and 450°C or less. Thereafter, the atmosphere in the chamber is made into a reducing atmosphere containing hydrogen. Specifically, the hydrogen concentration may be 500ppm or more and 50000ppm or less. It is preferable that the hydrogen concentration is 1000ppm or more and 30000ppm or less. There is no particular limit to the gas contained in the atmosphere other than hydrogen. For example, argon gas or nitrogen gas may be used. However, the oxygen concentration is less than 50ppm. Then, after the atmosphere is adjusted to a reducing atmosphere, it is maintained at the temperature at which the reduction treatment is performed for a predetermined time. There is no particular limit to the predetermined time. For example, the time is set to 0.5 hours or more and 3.0 hours or less. After that, the inside of the chamber is cooled to room temperature while maintaining the reducing atmosphere. There is no particular limit to the cooling rate. For example, the cooling rate may be set to 1° C. / min or more and 100° C. / min or less.
[0067] In addition to the above-mentioned single roll method, the soft magnetic alloy according to the present embodiment can be obtained by, for example, water atomization or gas atomization. The gas atomization method will be described below.
[0068] In the gas atomization method, a molten alloy is obtained at 1200 to 1500° C. in the same manner as in the single roll method described above.Then, the molten alloy is sprayed in a chamber to produce powder.
[0069] The gas heating temperature may be from 4 to 100°C, and is preferably from 4 to 30°C.
[0070] The atmosphere inside the chamber may be any atmosphere, for example, a vacuum or air, or an argon atmosphere with vapor pressure controlled by dew point adjustment.
[0071] After the powder is produced by the gas atomization method, a heat treatment is carried out in which the above-mentioned first to third steps are carried out consecutively, as in the case of the single roll method.
[0072] Although one embodiment of the present invention has been described above, the present invention is not limited to the above embodiment.
[0073] There is no particular limitation on the shape of the soft magnetic alloy according to the present embodiment. As described above, examples include a ribbon shape and a powder shape, but other shapes such as a thin film shape and a block shape are also possible.
[0074] There is no particular limitation on the applications of the soft magnetic alloy according to this embodiment, and examples thereof include magnetic parts such as magnetic cores, thin film inductors, magnetic heads, and transformers. EXAMPLES
[0075] The present invention will be specifically described below with reference to examples.
[0076] (Experimental Example 1) The atomic ratio of the composition is Fe 0.825 Nb 0.060 Cu 0.005 B 0.080 P 0.030The various raw metals were weighed out so as to obtain a master alloy with the above composition. After evacuating the chamber, the master alloy was melted by high-frequency heating to produce the master alloy. The above composition satisfies a=0.060, b=0.005, c=0.110, d=0, α=0, and β=0. In other words, the C content of the master alloy is ave is 0.5 at%.
[0077] The mother alloy thus prepared was then heated and melted to obtain a molten metal at 1300°C, after which the metal was sprayed onto a roll by a single roll method to produce a ribbon. The roll temperature was 60°C, and the atmosphere in the chamber was air. The thickness of the ribbon obtained was 20 μm by appropriately adjusting the rotation speed of the roll.
[0078] Next, each of the produced ribbons was subjected to a heat treatment to obtain a monolithic sample. The heat treatment was carried out by successively carrying out the first to third stages described below.
[0079] In the first stage, the atmosphere in the chamber was first set to a nitrogen atmosphere with an O concentration shown in the "1st" column of Tables 1A to 1E. In other words, an oxidizing atmosphere was set. The H concentration in the atmosphere at this time was less than 50 ppm. Then, the temperature in the chamber was increased to the temperature shown in the "1st" column of each table. The heating rate was 10°C / min. Then, the temperature and atmosphere shown in the "1st" column of each table were maintained for the time shown in the "1st" column of each table.
[0080] In the second stage, first, while maintaining the temperature shown in the "1st" column of each table, the atmosphere in the chamber was changed to the atmosphere shown in the "2nd" column, in which the O concentration was less than 50 ppm and the H concentration was less than 50 ppm. In other words, an inert atmosphere was used. Then, the temperature in the chamber was increased to the temperature shown in the "2nd" column of each table. The heating rate was 10°C / min. Then, the temperature shown in the "2nd" column of each table was maintained for the time shown in the "2nd" column of each table.
[0081] In the third stage, first, the temperature in the chamber was lowered to the temperature shown in the "3rd" column of Tables 1A to 1E while maintaining the inert atmosphere in the second stage. The cooling rate was 10°C / min. Then, the atmosphere in the chamber was changed to a nitrogen atmosphere having a H concentration shown in the "3rd" column of each table. In other words, a reducing atmosphere was used. The O concentration in the atmosphere at this time was less than 50 ppm. Then, the temperature shown in the "3rd" column of each table was maintained for the time shown in the "3rd" column of each table.
[0082] Thereafter, the inside of the chamber was cooled to room temperature while maintaining the reducing atmosphere at a cooling rate of 10°C / min.
[0083] Each sample was observed using a 3DAP. First, a needle-shaped sample with a diameter of 100 nm x 200 nm was prepared for each sample. Next, an observation range of 40 nm x 40 nm x 200 nm was set for the needle-shaped sample. The set observation range was divided into a grid of 320,000 cubic pieces of 1 nm x 1 nm x 1 nm.
[0084] The Cu concentration was measured for each grid on an atomic basis. The Cu concentration for each sample was calculated by averaging the Cu concentrations for all grids. ave In Experimental Example 1, it was confirmed that the C ave was 0.5 at%.
[0085] Elemental mapping of Cu was performed using 3DAP, and it was confirmed that multiple Cu clusters were included in the observation range. The sphere-equivalent diameter of each Cu cluster included in the observation range was measured, and the average was calculated. It was confirmed that the average sphere-equivalent diameter of the Cu clusters included in the observation range was 3.0 nm or more and 30 nm or less in all the soft magnetic alloys of the examples.
[0086] Furthermore, for each Cu cluster in the observation area, max The A / B ratios were measured for each Cu cluster in the observation area, and the average and variance (σ 2 The results are shown in each table.
[0087] The Bs of each sample was measured. Specifically, it was measured in a magnetic field of 1000 kA / m using a vibrating sample magnetometer (VSM). The results are shown in each table.
[0088] It was confirmed by XRD that the soft magnetic alloys of all the examples had a crystalline phase and an amorphous phase.
[0089] Next, magnetic cores (toroidal cores) were made using the ribbons of each sample of soft magnetic alloy. First, five toroidal pieces with an outer diameter of 18 mm and an inner diameter of 10 mm were punched out of the ribbons, and the punched ribbon pieces were stacked to obtain a toroidal core with a height of approximately 0.1 mm.
[0090] Next, the core loss of the obtained toroidal core was measured. Specifically, a BH analyzer (SY-8218 manufactured by Iwatsu Measuring Instruments) was used to measure the magnetic flux density at 60 mT and the measurement frequency at 600 kHz. The degree to which the core loss of the toroidal core made from each sample had decreased compared to the core loss of the toroidal core made from the sample (sample 1-1 in Experimental Example 1) made under the same conditions except that the heat treatment was performed by performing only the second stage without performing the first and third stages was calculated as the core loss reduction rate. The results are shown in each table. A core loss reduction rate of 5.0% or more was considered good, and a core loss reduction rate of 8.0% or more was considered even better.
[0091] [Table 1A]
[0092] [Table 1B]
[0093] [Table 1C]
[0094] [Table 1D]
[0095] [Table 1E]
[0096] In addition to sample 1-1, Table 1A lists examples in which the O concentration in the first stage or the H concentration in the third stage was changed. In each example, A / B was within the specified range. Compared to sample 1-1, which was performed only in the second stage, Bs was equivalent and the core loss was sufficiently reduced.
[0097] Table 1B lists examples in which the temperature and / or time of the first stage was changed from that of Sample 1-2 in Table 1A, and comparative examples in which the first stage was omitted and only the second and third stages were performed. In each example, A / B was within the specified range. In contrast, in each comparative example in which the first stage was omitted, A / B was outside the specified range.
[0098] In each of the examples, the core loss was sufficiently reduced compared to sample 1-1, which was subjected to only the second stage. In contrast, in each of the comparative examples, in which the first stage was omitted, Bs was equivalent and the core loss was increased compared to sample 1-1, which was subjected to only the second stage.
[0099] Table 1C lists examples in which the temperature and / or time of the second stage was changed from that of Sample 1-2 in Table 1A. In each example, A / B was within the specified range. Furthermore, compared to Sample 1-1, which was subjected to only the second stage, Bs was equivalent and the core loss was sufficiently reduced.
[0100] Table 1D lists examples in which the temperature and / or time of the third stage was changed from that of sample 1-2 in Table 1A, and comparative examples in which the third stage was omitted and only the first and second stages were performed. In each example, A / B was within the specified range. Furthermore, compared to sample 1-1 in which only the second stage was performed, Bs was equivalent and the core loss was sufficiently reduced. In contrast, in the comparative example in which the third stage was omitted, A / B was outside the specified range. Furthermore, compared to sample 1-1 in which only the second stage was performed, Bs was equivalent and the core loss increased.
[0101] Table 1E lists examples in which the temperature of the first stage, the time of the first stage, the temperature of the third stage, and the time of the third stage were changed from those of sample 1-2 in Table 1A. In each example, A / B was within the specified range. Furthermore, compared to sample 1-1, which was subjected to only the second stage, Bs was equivalent and the core loss was sufficiently reduced.
[0102] Table 1F shows a comparative example in which the first and third steps of sample 1-2 are interchanged. The heat treatment method of sample 1-54, a comparative example shown in Table 1F, will be described below.
[0103] In the first stage, a nitrogen atmosphere was created in which the H concentration was the concentration shown in the "1st" column of Table 1F. In other words, a reducing atmosphere was created. The O concentration in the atmosphere at this time was less than 50 ppm. Then, the temperature was increased to the temperature shown in the "1st" column of Table 1F. Then, the temperature and atmosphere shown in the "1st" column of each table were maintained for the time shown in the "1st" column of Table 1F.
[0104] In the second stage, first, while maintaining the temperature shown in the "1st" column of Table 1F, the atmosphere was changed to the atmosphere shown in the "2nd" column, in which the O concentration was less than 50 ppm and the H concentration was less than 50 ppm. In other words, an inert atmosphere was used. Then, the temperature was increased to the temperature shown in the "2nd" column of Table 1F. Then, the temperature shown in the "2nd" column of Table 1F was maintained for the time shown in the "2nd" column of Table 1F.
[0105] In the third stage, the temperature was lowered to the temperature shown in the "3rd" column of Table 1F while maintaining the atmosphere in the second stage. Then, the atmosphere was changed to a nitrogen atmosphere having an O concentration shown in the "3rd" column of Table 1F. In other words, an oxidizing atmosphere was created. The H concentration in the atmosphere at this time was less than 50 ppm. Then, the temperature shown in the "3rd" column of each table was maintained for the time shown in the "3rd" column of Table 1F. Then, the temperature was cooled to room temperature while maintaining the oxidizing atmosphere.
[0106] [Table 1F]
[0107] From Table 1F, in the comparative example in which the first and third stages were interchanged from sample 1-2, A / B was outside the specified range. Also, compared to sample 1-1 in which only the second stage was carried out, Bs was equivalent and the core loss increased.
[0108] (Experimental Example 2) In Experimental Example 2, the same procedures as for Samples 1-1 and 1-2 were carried out, except that part of Fe was replaced with Co and / or Ni. For some samples, the temperature in the second stage was adjusted. The results are shown in Tables 2A to 2C.
[0109] [Table 2A]
[0110] [Table 2B]
[0111] [Table 2C]
[0112] As can be seen from Tables 2A to 2C, results similar to those of Experimental Example 1 were obtained even when part of Fe was replaced with Co and / or Ni.
[0113] (Experimental Example 3) The same procedures were carried out as for samples 1-1 and 1-2, except that the type and / or content of element M was changed. For some samples, the temperature was adjusted in the second stage. The results are shown in Tables 3A to 3E. The content of element 1 is a1, the content of element 2 is a2, and a=a1+a2.
[0114] [Table 3A]
[0115] [Table 3B]
[0116] [Table 3C]
[0117] [Table 3D]
[0118] [Table 3E]
[0119] As can be seen from Tables 3A to 3E, results similar to those of Experimental Example 1 were obtained even when the type and / or content of the M element was changed.
[0120] (Experimental Example 4) The same procedures were carried out as for samples 1-1 and 1-2, except that the Cu content was changed. The results are shown in Table 4.
[0121] [Table 4]
[0122] From Table 4, it can be seen that the same results as in Experimental Example 1 were obtained even when the Cu content was changed.
[0123] (Experimental Example 5) The same procedure was carried out as for samples 1-1 and 1-2, except that the type and content of X1 were changed. The results are shown in Tables 5A to 5C. The content of B is c1, the content of P is c2, the content of Si is c3, and the content of C is c4, where c=c1+c2+c3+c4. The samples shown in Tables 5A and 5B do not contain Si or C.
[0124] [Table 5A]
[0125] [Table 5B]
[0126] [Table 5C]
[0127] As seen from Tables 5A to 5C, results similar to those of Experimental Example 1 were obtained even when the type and / or content of X1 was changed.
[0128] (Experimental Example 6) The same procedures were carried out as for samples 1-1 and 1-2, except that the type and content of X2 were changed. The results are shown in Table 6. The content of element 1 is d1, the content of element 2 is d2, and d=d1+d2.
[0129] [Table 6]
[0130] As can be seen from Table 6, the same results as in Experimental Example 1 were obtained even when the type and / or content of X2 was changed.
[0131] (Experimental Example 7) The same procedures were carried out as for Samples 1-1 and 1-2, except that the heat treatment temperature was appropriately changed for some compositions other than those used in Experimental Examples 2 to 6. The results are shown in Table 7.
[0132] [Table 7]
[0133] As can be seen from Table 7, results similar to those of Experimental Example 1 were obtained even when the composition and heat treatment conditions were changed.
[0134] (Experimental Example 8) The master alloy prepared under the same conditions as in Experimental Example 1 was heated and melted to become a molten metal at 1500°C, and then the gas heating temperature was set to 30°C, dew point-adjusted argon was filled into the chamber, and powder was produced by a gas atomization method. The resulting soft magnetic metal powder was classified by sieving so that the average particle size (D50) was 24 μm.
[0135] The obtained soft magnetic metal powder was subjected to a heat treatment under the same conditions as those for Samples 1-1 and 1-2 in Experimental Example 1.
[0136] For each sample obtained, Cu element mapping was performed using 3DAP in the same manner as in Experimental Example 1, and it was confirmed that a plurality of Cu clusters were included in the observation range. The sphere-equivalent diameter of each Cu cluster included in the observation range was measured, and the average was calculated. It was confirmed that the average sphere-equivalent diameter of the Cu clusters included in the observation range was 3.0 nm or more and 30 nm or less in all of the soft magnetic alloys of the examples.
[0137] Furthermore, for each Cu cluster in the observation area, max The A / B ratios were measured for each Cu cluster in the observation area, and the average and variance (σ 2 The results are shown in Table 8.
[0138] The Bs of each sample was measured in the same manner as in Experimental Example 1. The results are shown in Table 8.
[0139] As in Experimental Example 1, it was confirmed that the soft magnetic alloys of all the examples had a crystalline phase and an amorphous phase.
[0140] Next, magnetic cores (toroidal cores) were made using the soft magnetic metal powders of each sample. First, phenolic resin, which serves as an insulating binder, was mixed with each powder so that the amount of phenolic resin was 3% by mass of the total. Next, the powder was granulated using a general planetary mixer as an agitator to obtain granulated powder of about 500 μm. Next, the obtained granulated powder was subjected to a surface pressure of 4 ton / cm. 2 (392 MPa) to produce a toroidal compact with an outer diameter of 18 mm, an inner diameter of 10 mm, and a height of 6.0 mm. The obtained compact was cured at 150°C to produce a toroidal core.
[0141] Next, the core loss of the obtained toroidal core was measured. Specifically, using a BH analyzer (SY-8218 manufactured by Iwatsu Measuring Instruments), the measurement was performed with a magnetic flux density of 60 mT and a measurement frequency of 600 kHz. The degree to which the core loss of the toroidal core made from each sample was reduced compared to the core loss of the toroidal core made from the sample (sample 95-1 in Experimental Example 8) that was heat-treated under the same conditions except that the first and third stages were not performed and only the second stage was performed was calculated as the core loss reduction rate. The results are shown in Table 8. A core loss reduction rate of 5.0% or more was considered good, and a core loss reduction rate of 8.0% or more was considered even better.
[0142] For comparison, Table 8 shows the results of Samples 1-1 and 1-2, which were produced under substantially the same conditions as Samples 95-1 and 95-2, except that the alloy shape was a ribbon shape.
[0143] [Table 8]
[0144] From Table 8, it can be seen that the same results as in Experimental Example 1 were obtained even though the alloy was in powder form. [Explanation of symbols]
[0145] 11…Cu cluster 21... Line segment including Cu major axis 31…Nozzle 32… Molten metal 33... Roll 34… Thin ribbon 35…Chamber
Claims
1. A soft magnetic alloy containing at least Fe and Cu, The soft magnetic alloy includes at least one Cu cluster; In any cross section, the point where the Cu concentration is the highest in the Cu cluster is called point C, the longest diameter of the Cu cluster that passes through point C is called the Cu major axis, and the Cu concentration at point C is called C max year, The Cu concentration of the soft magnetic alloy is C ave year, The Cu major axis includes the point C, and the Cu concentration is continuously (0.5×C max ) is the length of the part that is equal to or greater than A, The Cu concentration is continuously increased by (2×C ave ) The length of the part that is equal to or greater than B, The soft magnetic alloy has an average A / B of 0.40 or more and 0.70 or less.
2. The dispersion of A / B in the soft magnetic alloy (σ 2 2. The soft magnetic alloy of claim 1, wherein σ is less than 0.
13.
3. C in the soft magnetic alloy max 3. The soft magnetic alloy according to claim 1, wherein the average of is 9.9 at % or more and 52.1 at % or less.
4. 3. The soft magnetic alloy according to claim 1, wherein the soft magnetic alloy has a crystalline phase and an amorphous phase.
5. 3. The soft magnetic alloy according to claim 1, which is in the form of a ribbon.
6. 3. The soft magnetic alloy according to claim 1, which is in powder form.
7. A magnetic component comprising the soft magnetic alloy according to claim 1 or 2.
Citation Information
Patent Citations
Magnetic core made of ultrafine crystalline alloy with excellent DC superimposition characteristics, manufacturing method thereof, and choke coil and transformer using the same
JP3287481B2
Nanocrystalline soft magnetic alloy
WO2021132254A1